2006
DOI: 10.3139/146.101263
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printing of TiAl3/Al2O3 composites

Abstract: Intermetallic/ceramic composites were fabricated by reactive infiltration of an Al melt into a porous TiO2 preform which was prepared by indirect three-dimensional printing. At 1450°C the highly negative Gibbs energy of reaction (Gr=–279.950kJ/mol) is the driving force for the redox reaction 13/2 Al+3/2 TiO23/2 TiAl3+Al2O3 to take place. Wetting of molten Al on the preform surface was improved by adding a carbon-bearing binder ((C6H10O5)n, dextrin) to the powder blend, which decomposed to amorphous carbon (car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…[85] Several research groups have intensively investigated the potential of manufacturing intermetallic/ceramic composites using a near-net-shape fabrication process involving infiltration of porous preforms fabricated by means of 3DP. Yin et al applied agglomerated powders [86] and freeze-dried granules [53,54] from TiC/TiO2/dextrin mixtures with varying blending ratios. Although the particle size of the feedstocks was comparable, the use of freeze-dried granules reduced the porosity of printed objects from 65% to 55%.…”
Section: Three-dimensional Printing (3dp)mentioning
confidence: 99%
“…[85] Several research groups have intensively investigated the potential of manufacturing intermetallic/ceramic composites using a near-net-shape fabrication process involving infiltration of porous preforms fabricated by means of 3DP. Yin et al applied agglomerated powders [86] and freeze-dried granules [53,54] from TiC/TiO2/dextrin mixtures with varying blending ratios. Although the particle size of the feedstocks was comparable, the use of freeze-dried granules reduced the porosity of printed objects from 65% to 55%.…”
Section: Three-dimensional Printing (3dp)mentioning
confidence: 99%
“…Dense SiSiC was obtained by subsequent pyrolysis and pressureless liquid silicon melt infiltration [18]. Yin et al [19] built TiAl 3 /Al 2 O 3 composites by reactive infiltration of an Al melt into a porous TiO 2 preform which was prepared by indirect three-dimensional printing. Nan et al [20] reported the near-net-shape manufacturing of Ti 3 SiC 2 -based ceramics by three-dimensional printing combined with liquid silicon infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…While rapid prototyping methods have been used to prepare porous preforms for other reactive infiltration processes, no work has been conducted to date on the integration of rapid prototyping methods with a reactive infiltration process capable of generating dense, near net-dimension, ultrahigh-melting (>2500 • C) ceramic/metal composites. [38][39][40][41][42] The purpose of this paper is to evaluate the use of two rapid prototyping methods, 3D printing and computernumerical-controlled (CNC) machining, for fabricating shaped, porous WC preforms for subsequent conversion into dense, near net-shape/net-dimension ZrC/W-based composites.…”
Section: Introductionmentioning
confidence: 99%